Atractyloside Protect Mice Against Liver Steatosis by Activation of Autophagy via ANT-AMPK-mTORC1 Signaling Pathway - Zhang, Pengfei; Cheng, Xinyu; Sun, Huimin; Li, Yajing; Mei, Wuxuan; Zeng, Changchun (Frontiers in Pharmacology, 2021)
Objective: Adenine nucleotide translocase (ANT) can transport ADP from cytoplasm to mitochondrial matrix and provide raw materials for ATP synthesis by oxidative phosphorylation; its dysfunction will lead to limitation of ADP transport and decrease of ATP production. Atractyloside (ATR) can competitively bind to ANT with ADP, makes ANT vulnerable to transport ADP and reduces ATP synthesis; which is considered to be cytotoxic. However, the blockage of ANT by ATR may increase ADP/ATP ratio, activate AMPK, inhibit mTORC1, induce autophagy activation, and promote lipid degradation in steatosis hepatocytes. The present study was conducted to investigate the mechanism of ATR regulates ANT-AMPK-mTORC1 signaling pathway to activate autophagy, and promotes the degradation of lipid droplets in HFD-induced liver steatosis. Methods: ICR mice were fed with high-fat diet for 8 weeks to induce the liver steatosis, and ATR solution was given by intraperitoneal injection for the treatment. Intracellular triglyceride level and Oil Red O staining-lipid droplets (LDs) were assessed, the protein level related to ANT2-AMPK-mTORC1 signaling pathway and autophagy, and the co-localization of LC3B and Perilipin 2 was performed. Results: ATR treatment decreased the serum AST level, relative weight of liver and epididymal fat, and body weight of HFD mice. The LDs in HFD mice liver were reduced in the presence of ATR, and the TG level in serum and liver of HFD mice was significantly reduced by ATR. In addition, ATR inhibits ANT2 expression, promotes the activation of AMPK, and then increased Raptor expression, finally decreased the mTOR activity. Furthermore, ATR increased protein level of LC3A/B and ATG7, and a strong colocalization of LC3B and PLIN2 was observed. Conclusion: ATR treatment could block ANT2 expression, promotes the activation of AMPK, then decreased the mTOR activity, finally promote autophagosomes formation, thus accelerate the degradation of HFD-induced accumulated lipids in the liver. This will provide new therapeutic ideas and experimental data for clinical prevention and treatment of non-alcoholic fatty liver disease.